Quantum Dot Sensitized Whisperonic Solar Cells—Improving Efficiency Through Whispering Gallery Modes - Cholasettyhalli Dakshinamurthy, Athrey; Das, Tapan Kumar; Ilaiyaraja, P.; Sudakar, Chandran (Frontiers in Materials, 2019)
Environmental deterioration and depletion in conventional energy resources greatly demand the need for photovoltaic devices, which use solar radiation to meet future energy demands. Efficient light management plays a pivotal role in improving the performance of photovoltaic devices. Various avenues have been explored to address light management in solar cells. Employing whispering gallery mode (WGM) microresonators in solar cell device is one such strategy. Using resonating structures for light scattering is recently gaining momentum as they exhibit great potential to enhance the efficiency through light trapping. Functional material based microresonators further provide added advantage as they combine inherent optical resonance with the material properties suitable for photovoltaics like efficient charge separation and transport in one platform. “Whisperonic solar cell” is a broadly classified device in which resonating cavities are used in the cell architecture to effectively scatter the light, resulting in enhanced light absorption and thus efficiency. Recent studies reveal that WGM enabled optical microcavities can effectively get coupled to the light absorber in a sensitized solar cell (SSC) and improve the performance of SSC significantly. In this short review, we briefly present the idea of enhancing the efficiency of solar cell using whispering gallery modes. Several case studies available from the literature for realizing the concept of WGM for light trapping are highlighted. Particular focus is given to the quantum dot sensitized whisperonic solar cells. The concept is much more universal and will be useful both in thin film and sensitizer solar cells.